Melalui Pembelajaran Metode Bermain Peran Untuk Meningkatkan Aktivitas dan Hasil Belajar IPA Pada Siswa Kelas VI SDN 1 Seraya Barat - I Komang Suryasa (Jayapangus Press, 2021)
The implementation of good learning cannot be separated from the learning process which consists of interactions between teachers and students in exploring teaching materials and media. The problem is whether the implementation of learning using the role-playing method can improve science learning activities and outcomes in class VI students in semester I at SDN 1 Seraya Barat for the 2019/2020 academic year? The subjects of this study were students of Class VI Semester I SDN 1 West Seraya with a total of 27 people. For the purposes of data collection, observation methods and measurement sheets were used. The data obtained were analyzed using descriptive qualitative analysis techniques. Based on the data analysis, it can be concluded that the Role Playing Method can improve the activities and learning outcomes of science subjects. This is evidenced by the increase in science learning activities for Class VI students in Semester I at SDN 1 Seraya Barat with the average activity value increasing from 73.46 in the first cycle to 84.57 in the second cycle and the average learning outcome from 69.55 in the first cycle to 85. 80 in the second cycle with the second cycle activity completeness 85.19% and the second cycle learning outcomes 88.89%. From the results of the Classroom Action Research, researchers will continue similar activities to improve the quality of learning in schools.